1984
DOI: 10.1007/bf01461486
|View full text |Cite
|
Sign up to set email alerts
|

Similarity solutions for buoyancy induced flows in a saturated porous medium adjacent to impermeable horizontal surfaces

Abstract: Abstract. In the present paper similarity solutions for the convective flow induced by buoyancy in a saturated porous medium adjacent to horizontal impermeable surfaces are obtained. The analysis incorporates the variation of permeability from the wall and expressions for boundary layer thickness, local and overall surface heat-flux are obtained. Applications of the results to convective flows in a geothermal reservoir are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In some applications, such as fixed-bed catalytic reactors, packed bed heat exchangers and drying, the porosity is not uniform but has a maximum value at the wall and a minimum value away from the wall. This wall-channeling phenomenon has been reported by a number of investigators such as Vafai [6], Chandrasekhara et al [7], Chandrasekhara [8], and Hong et al [9] for forced, natural, and mixed convection boundary layer flows adjacent to a horizontal and vertical surfaces. It is shown that the variable porosity effect increases the temperature gradient adjacent to the wall resulting in the enhancement of the surface heat flux.…”
Section: Introductionsupporting
confidence: 59%
“…In some applications, such as fixed-bed catalytic reactors, packed bed heat exchangers and drying, the porosity is not uniform but has a maximum value at the wall and a minimum value away from the wall. This wall-channeling phenomenon has been reported by a number of investigators such as Vafai [6], Chandrasekhara et al [7], Chandrasekhara [8], and Hong et al [9] for forced, natural, and mixed convection boundary layer flows adjacent to a horizontal and vertical surfaces. It is shown that the variable porosity effect increases the temperature gradient adjacent to the wall resulting in the enhancement of the surface heat flux.…”
Section: Introductionsupporting
confidence: 59%
“…where K 0 is the value of the permeability at the edge of the boundary layer, a* is a constant having dimensions of length and d* is a constant whose value is taken to be 3 after Chandrasekhara [10]. The expressions for' )~m (Y) and c~ (y) tbllowing (after Chandrasekhara et al [10]) are…”
Section: K(y)mentioning
confidence: 99%
“…It is found from the Table 1 that the thickness A of the second boundary layer is always greater than the thickness of the first boundary layer 6 since ~ is greater than unity for all values of B. The values of B, the dimensionless porous parameter are kept low since the permeability at the wall increases due to the packing of the particles (see Chandrasekhara and Votmeyer [6], Benenati and Brosilow [7] Chandrasekhara et al [8], Chandrasekhara [9] and Chandrasekhara and Namboodiri [10]. However, it is observed from the results that the value of 4 does not …”
Section: --2at +A~o~176 B~-o~mentioning
confidence: 98%